The Impact of Dynamic Capabilities on competitive advantage Analytical research in Iraqi Cement State Company - حامد سهير عادل; حنان صفاء كامل (Journal of Economics and Administrative Sciences, 2019)
The current research aims to diagnose the nature of the relation between dynamic capabilities as an independent variable and competitive advantage as a respondent variable, and identify the role of each of them in achieving the required performance of the organizations and adapt to the rapid environmental changes. The research was applied to the Iraqi Cement State Company one of the formations of the Iraqi Ministry of Industry and Minerals, and based on the importance of the subject matter of the research and the importance of the research sample and company of inquiry, The researcher adopted the descriptive analytical method in completing his research. The sample of the research was Intentional sample (75) individual from the leaders of the companies included (General Managers, General Managers Assistants, Department Managers and division Directors), by using the questionnaire as the main tool for data collecting and information which consisted of (39) paragraphs. In order to process the data and test the hypotheses, many statistical methods were used such as (Alpha Kronbach factor, confirmatory factor analysis, One Way Anova, and others), the results were extracted using the computer’s program (Spss V.23, Amos V.23), then the research results with a set of conclusions, which proved the validity of the hypotheses and the most important that the dynamic capabilities affects directly the competitive advantage,